Pengaruh Kunjungan Wisatawan, Luas Artshop dan Lokasi Artshop Terhadap Penyerapan Tenaga Kerja Bisnis Artshop di Kawasan Nusa Dua - Ayu Darsini, Ni Nyoman; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 5, Mei 2014 (pp.173- 226), 2014)
Nusa Dua tourism area known as the most visited by tourists. The number of tourists who visit resulted in the majority of the people's livelihood Nusa Dua turning to the informal sector. Artshop business deployment there is form a group and there are also scattered around the area in Nusa Dua. The benefit of this study was to determine the effect of simultaneously and partially between tourist visits, extensive art shops, and the location of the business employment artshop in Nusa Dua area. In this study using primary data, then analyzed with multiple linear regression method. The results is indicate that tourist visits, extensive art shops and locations artshop significant effect on the business employment artshop in Nusa Dua area, either simultaneously or partially.
Keywords: tourism arrivals; extensive artshop; located artshop; employment